Yashadamritamalaharam Application in the Management of Parikarthika - A Comprehensive Analytical Review (International Journal of Ayurveda and Pharma Research, 2024)
Parikartika is one among the anorectal diseases, which can be correlated with fissure in ano in the contemporary medicine. Parikartika is a disease condition rather than a single entity disease, which is usually triggered by other factors as per Ayurveda classics. It is usually described as a very painful condition which mostly affects the quality living. The disease pathology should be analyzed, studied and appropriate therapeutic measures should be advised to tackle and prevent the recurrence. There are many therapeutic methods available today for the treatment of Parikartika both in modern and Ayurveda. Modern methods are no replace oral pain medications, topical ointments, botulin injections surgical interventions etc. These have usually side effects and cause inconvenience to the patients. Ayurvedic preparations are also very effective, out of which a convenient, patient friendly easy method must be chosen. Yashadamrita malahara is a Malahara preparation from classical rasa text Rasatarangini which has wound healing properties which can be applied as an ointment or as Pichu. Aims and Objectives: This is an in-depth review analysis of Parikartika samprapti and the effect of Yashadamrita malahara in the management of the disease. Materials and methods: An attempt has been made to analyze the Samprapti ghatakas of Parikartika and the pharmacological actions of Yashadamrita malahara, and to explain the probable mode of action of the drug in the disease. Discussion and conclusion: Evaluation of the effect of Yashadamrita malahara and its therapeutic benefits in Parikartika by its mode of action.